Design strategies for non-residential zero-energy buildings: lessons learned from Task40/Annex 52: towards net zero-energy solar buildings - Aelenei, Daniel (2014)
Net zero-energy buildings (Net ZEBs) have been the object of various studies in recent years as various countries have set this performance as long-term goal of their energy policies. Designing successful Net ZEBs represents a challenge since the definitions are yet generic, the assessment method and monitoring approach are under development and the literature is relatively scarce about the best sets of solutions for different typologies and climates likely to deliver an actual and reliable performance in terms of energy balance (used consumed vs. generated) on a costeffective basis. The International collaborative research initiative between the Solar Heating and Cooling (SHC) and the Energy Conservation in Buildings and Community Systems (ECBCS) through Task 40/Annex 52 - Towards Net-Zero Energy Solar Buildings-, summarises most of the recent developments in this field. The authors of this article, who are participants in this task, are providing insights from on-going research work on some best practice leading projects which have been the object of an exploratory cross-case analysis in order to facilitate identification of the set of relevant design strategies. The close inspection of the strategies and indicators of the relative performance of the projects revealed interesting features about the combination of design challenges with techniques and technologies responsible for delivering the Zero Energy performance.